Репрезентативність природно-заповідного фонду на Львівщині та шляхи створення його оптимальної мережі - Стойко, С.; Петрова, Л. (Праці наукового товариства ім. Шевченка, 2001)
Дано аналіз сучасної структури природно-заповідного фонду та оцінку його репрезентативности у природних районах Львіщини. Обґрунтовано функціональну систему заповідних територій, пов’язаних екологічними коридорами. Пропонується створити нові реґіональні ландшафтні парки рекреаційного призначення. Для охорони історико-культурної спадщини обґрунтовано категорію ландшафтно-меморіальних парків. The system of the protected territories in Lviv region includes 342 objects with total area of 113197 ha (5,2 % of the whole region territory). The authors have analyzed the representativity of the natural protected fund (NPF). It has been established that such
physical-geographical regions Precarpathian, Opillya, Polissya NPF does not include all
landscape diversity. Therefore it has been proposed to widen the net of protected areas. It is desirable to preserve not only the natural heritage but also the historical and cultural ones. In this purpose the preservation of localities involved into events of World War I and II is proposed. The authors propose to create 3 landscape natural parks: Shashkewich mountain, Makivka mountain and Brodiwski.